EFFICACY OF THORACOSCOPIC SURGERY AND CONVENTIONAL OPEN SURGERY FOR CONGENITAL DIAPHRAGMATIC HERNIA IN NEONATES - Huseynov, F.R. (World of Medicine and Biology, 2025)
With the purpose of the study was a comparative analysis of the effectiveness of traditional laparotomy and video-assisted thoracoscopic surgery in the treatment of congenital diaphragmatic hernia in newborns 70 newborns (1st group – 44 newborns, operated on using the traditional open method; the 2nd group – 26 newborns, operated on using endosurgery) were observed. According to results, the Apgar score at the 1st minute in the 2nd group was 5.42±0.22 points, and in the 1st group – 5.66±0.17 points (p=0.3943). Similar distinctive features in the data were observed in the groups at the 5th minute after birth: 8.35±0.14 and 8.64±0.11 points, respectively (p=0.1118). The quality of life of children after surgical treatment of diaphragmatic hernia, both by the total score and by all scales, was significantly higher than before the treatment of the pathology (p0.05).
Keywords: children; congenital diaphragmatic hernia; open access; thoracoscopy; quality of life